(untitled) (Transport systems and technologies, 2019)
The locomotive driver constantly evaluates the current situation and makes managerial decisions that are in line with his main task - safe and efficient driving. Intellectual activity of the person at the same time is rather complex and can not be accurately described in the expressions of classical mathematics. The analysis of the effects on the locomotive driver in the control of the train is carried out, methods of fuzzy mathematics for the description of the train situations are offered. The current train situation is presented in the form of a fuzzy situation, which is compared with all typical situations that are in the memory of the intellectual system. A typical situation is determined which is closest to the input and the system makes a decision that corresponds to a certain typical situation. This approach allows us to implement the fastest and most straightforward algorithm for determining the state of the train while driving for an intelligent control system.